Uncertainty and its discontents : worldviews in world politics - Katzenstein, Peter J. (Cambridge studies in international relations., 2022)
This volume provides the first major study of worldviews in international relations. Worldviews are the unexamined, pre-theoretical foundations of the approaches with which we understand and navigate the world. Advances in twentieth century physics and cosmology and other intellectual developments questioning anthropocentrism have fostered the articulation of alternative worldviews that rival conventional Newtonian humanism and its assumption that the world is constituted by controllable risks. This matters for coming to terms with the uncertainties that are an indelible part of many spheres of life including public health, the environment, finance, security and politics - uncertainties that are concealed by the conventional presumption that the world is governed only by risk. The confluence of risk and uncertainty requires an awareness of alternative worldviews, alerts us to possible intersections between humanist Newtonianism and hyper-humanist Post-Newtonianism, and reminds us of the relevance of science, religion and moral values in world politics.